Cloud computing adoption in Ghana; accounting for institutional factors. (May 2021) - Adjei, Joseph K.; Adams, Samuel; Mamattah, Lovestone
Abstract: In spite of increasing adoption of Cloud Computing (CC) by organizations in developed countries, the rate of adoption of the technology in sub-Saharan Africa has stagnated, although it has the potential to accelerate the speed of digital transformation. This paper contributes to the extant literature in this light by examining how the institutional environment influences the adoption of cloud computing. We investigated the role of mimetic, coercive and normative institutional pressures in predicting adoption outcomes of cloud computing among organizations in the region. After testing three main hypotheses and ten corollaries, and analyzing data collected from seventy-nine organizations with the partial least square structural equation modelling (PLS-SEM), the study found that the institutional pressures (mimetic, coercive and normative) explain 27% of the variance in cloud computing adoption. The mimetic – CC adoption path coefficient of 0.35 made the biggest contribution to the model while the normative – CC adoption path was the least contributor with a path coefficient of 0.18. The findings explain the determinants of adoption of CC in environments of low adoption and institutional challenges. Highlights: Institutional factors influence organizational behavior towards adoption of Cloud Computing in Ghana. Perceptions about the nature of prohibitions placed on data transfer is very important in shaping Cloud Computing adoption. Models of IT adoption may should not be imported wholesale from one context to another. The view that Cloud Computing is a fashion promoted by interest groups as status symbol is unsupported.